Improving the model of a system that maintains a microclimate regime in a single-family house by using a reversible heat pump - Shavolkin, Oleksandr; Shvedchykova, Iryna; Demianchuk, Oleksandr; Shcherbakov, Oleg (Eastern-European Journal of Enterprise Technologies, 2025)
This study mathematically models energy processes within the microclimate control system in a single-family house equipped with a reversible heat pump. This paper reports an improved model of the microclimate system considering the dynamics to construct plots of electricity consumption under various operating conditions. Data from the calculated thermal parameters of the building were applied. A model of the reversible heat pump has been proposed, based on manufacturer specifications, allowing for the assessment of electricity consumption across the full range of power and temperature variations. The microclimate system model of the building with a heat pump has been improved by accounting for the building’s thermal inertia. This makes it possible to evaluate temperature regimes and energy consumption under dynamic modes, bringing the simulated electricity usage closer to real-world values. Hourly profiles of solar radiation and outdoor temperature for the building’s location, along with expected schedules of internal heat gains, were used. Energy consumption and instantaneous power values, including peak loads, were assessed. It is shown that, for a building in Kyiv with a floor area of 120 m2, under a heating mode, minimum electricity consumption occurs at a minimum heat carrier temperature of 35°C at a COP of 3.44. The selected heat pump may operate under a monovalent mode down to –13°C. The potential for reducing energy consumption by adjusting the temperature regime is limited because of a significant increase in power demand from the heat pump under a dynamic mode. Under a cooling mode, hourly air temperature profiles from historical data were used, along with representative values, to evaluate the range of energy consumption variation. An example involving changes in window area demonstrates the model’s applicability for adjusting building parameters to reduce energy consumption